2022
DOI: 10.3390/biology12010015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Activity of Ginkgo biloba—An Insight from Healthy Subjects

Abstract: Ginkgo biloba is the oldest living tree species in the world. Despite less than encouraging clinical results, extracts from its leaves are among the most used herbal preparations in the prevention and treatment of cardiovascular diseases. Most data on the efficacy of Ginkgo biloba on cardiovascular disease is from clinical studies, with few results from healthy subjects. This paper aims to provide a comprehensive review of the mechanisms underlying the known beneficial cardiovascular activities of Ginkgo bilob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 130 publications
0
10
0
Order By: Relevance
“…Ginkgetin is a natural flavonoid compound derived from the Ginkgo biloba . It exhibits pharmacological activities such as neuroprotection ( Singh et al, 2019 ), cardiovascular protection ( Silva and Martins, 2022 ), anti-oxidant ( Li et al, 2022d ), and anti-inflammatory effects ( Li et al, 2022b ). Additionally, research has shown that it exerts anti-cancer effects by inhibiting cell proliferation, angiogenesis, and inducing apoptosis in tumor cells ( DeFeudis et al, 2003 ; Ye et al, 2007 ; Bai et al, 2015 ; Han et al, 2016 ; Kim et al, 2021 ).…”
Section: Natural Products Modulating Ferroptosis For Intervention In ...mentioning
confidence: 99%
“…Ginkgetin is a natural flavonoid compound derived from the Ginkgo biloba . It exhibits pharmacological activities such as neuroprotection ( Singh et al, 2019 ), cardiovascular protection ( Silva and Martins, 2022 ), anti-oxidant ( Li et al, 2022d ), and anti-inflammatory effects ( Li et al, 2022b ). Additionally, research has shown that it exerts anti-cancer effects by inhibiting cell proliferation, angiogenesis, and inducing apoptosis in tumor cells ( DeFeudis et al, 2003 ; Ye et al, 2007 ; Bai et al, 2015 ; Han et al, 2016 ; Kim et al, 2021 ).…”
Section: Natural Products Modulating Ferroptosis For Intervention In ...mentioning
confidence: 99%
“…The herbs ginseng , ginkgo biloba , ganoderma lucidum , and gynostemma pentaphyllum have been reported to prevent CVDs [ 92 , 93 ]. These herbs are becoming more and more well-known due to their presence in commercial commodities in numerous markets around the world and their established therapeutic potential in a variety of settings, including cardiovascular conditions [ 92 ].…”
Section: Cardiovascular Health and Herbal Medicinementioning
confidence: 99%
“…These organic compounds profoundly alter important cellular, molecular, and metabolic processes that regulate the etiology and pathogenesis of CVDs [ 94 ]. Recent research shows that these herbal remedies have strong therapeutic effects and can improve pathological diseases linked to CVDs [ 92 , 93 ]. Clear clinical therapeutic advantages have not, however, been established.…”
Section: Cardiovascular Health and Herbal Medicinementioning
confidence: 99%
“…These secondary metabolites confer ginkgo with important medicinal value; for instance, the abundant flavonoids, terpene lactones, and other active substances present in ginkgo leaves have made ginkgo leaf extract a focus of attention in the herbal medicine industry. To date, the exploitation of ginkgo has mainly focused on using ginkgo leaf extract to develop health care and pharmaceutical products with good therapeutic effects on heart disease, coronary heart disease, senile dementia, nervous system diseases and many other chronic and acute diseases [5][6][7][8]. The current main method for obtaining active substances is still to extract them from ginkgo leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [14] summarized the practical significance and application of an extraction method with significant advantages, such as the supercritical carbon dioxide fluid extraction (SFE-CO 2 ) method, which can be employed in the extraction and separation of active ingredients in ginkgo leaves, seeds, pollen, and roots to make full use of ginkgo's resources. Finally, the effects on cardiovascular activity and potential adverse reactions to ginkgo leaf extract were summarized, and the safety of its potential clinical application was also demonstrated [6].…”
Section: Introductionmentioning
confidence: 99%